Dynamic panel estimator for Thailand's tourism demand - Leurcharusmee S. (2017)
© 2016 International Information Institute. This paper models Thailand's tourism demand from 24 origin countries and estimates its price, income and cross-price elasticities using Arellano and Bond (1991)'s dynamic panel estimator. The results are slightly different between the demand from Southeast Asian countries and that from other origin countries. The GDP has the greatest impact toward the growth rate of Thailand's tourism demand from origin countries outside Southeast Asia. However, it does not have a statistically significant effect on the demand from Southeast Asian countries. In addition to the effect of income changes, other factors that affect Thailand's tourism demand are homogeneous across origin counties. Specifically, the demand also responds to changes in exchange rate with respect to both Thailand and Asian substitute destinations. Moreover, the coefficients of all lagged variables of both dependent and explanatory variables are not statically significantly, indicating that the growth rate of the demand from last year does not affect the growth rate of the demand this year. It also indicates that price and income shocks affect Thailand's tourism demand immediately within the year.